Sensation : the new science of physical intelligence - Lobel, Thalma. (Atria Books, 2014)
"Like the revolutionary bestsellers Predictably Irrational and Emotional Intelligence, Sensation is an exciting, completely new view of human behavior--a new psychology of physical intelligence (or embodied cognition)--that explains how the body unconsciously affects our everyday decisions and choices, written by one of the world's leading psychologists. From colors and temperatures to heavy objects and tall people, a whole symphony of external stimuli exerts a constant influence on the way your mind works. Yet these effects have been hidden from you--until now. Drawing on her own work as well as from research across the globe, Dr. Thalma Lobel reveals how shockingly susceptible we are to sensory input from the world around us. An aggressive negotiator can be completely disarmed by holding a warm cup of tea or sitting in a soft chair. Clean smells promote moral behavior, but people are more likely to cheat on a test right after having taken a shower. Red-colored type causes us to fail exams, but red dresses make women sexier and teams wearing red jerseys win more games. We take questionnaires attached to heavy clipboards more seriously and believe people who like sweets to be nicer. Ultimately, the book's message is startling: Though we claim ownership of our decisions, judgments, and values, they derive as much from our outside environment as from inside our minds. Now, Sensation empowers you to evaluate those outside forces in order to make better decisions in every facet of your personal and professional lives"--